2023
DOI: 10.3390/plants12122349
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Characterization of GATA Transcription Factors in Liriodendron chinense and Functional Validation in Abiotic Stresses

Abstract: The Liriodendron chinense in the Magnoliaceae family is an endangered tree species useful for its socio-economic and ecological benefits. Abiotic stresses (cold, heat, and drought stress), among other factors, affect its growth, development, and distribution. However, GATA transcription factors (TFs) respond to various abiotic stresses and play a significant role in plant acclimatization to abiotic stresses. To determine the function of GATA TFs in L. chinense, we investigated the GATA genes in the genome of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…The effect of drought on longan was found to contribute to higher yields and higher economic returns. The GATA showed a close association with drought stress [14,46,47]. In a study of wheat GATA, we found that ABA with Ca 2+ caused the up-regulation of TaGATAs, which activated related genes [48].…”
Section: Discussionmentioning
confidence: 84%
“…The effect of drought on longan was found to contribute to higher yields and higher economic returns. The GATA showed a close association with drought stress [14,46,47]. In a study of wheat GATA, we found that ABA with Ca 2+ caused the up-regulation of TaGATAs, which activated related genes [48].…”
Section: Discussionmentioning
confidence: 84%